Prevalence of abnormal bone mineral density in HIV_postive patients in Ibadan, Nigeria (2013)
"Background:There have been reports of high rate of abnormal bone mineral densities (BMD) among people living with HIV. Following the introduction of combination antiretroviral therapy (CART) into Nigeria, the country is now home to increasing population of HIV positive patients. There is paucity of data about osteoporosis/osteopaenia and bone mineral density in this population. Aim and objectives:The aim of the study was to determine the prevalence and determinants of osteopaenia/osteoporosis in a cohort of HIV-positive patients in Nigeria. Patients and methods:The BMD of a group of patients attending the outpatient clinic of the University of Ibadan, Nigeria was assessed using a DXA machine. The relationship of bone mineral density to body weight, CART status, protease inhibitor use, and gender was investigated. Their CD4 counts and viral load were also estimated. RESULTS:A total of 1005 patients participated with a mean age of 41.3 ± 10 years. There were 724 females (72.0%) and 29.7% were single. The median length of diagnosis was 2 years (Range 1-18 years). The Median CD4 count was 371cells/ml and Median viral load was 200 copies/ml. Of this sample, 785 (78.1%) were on CART with 99 (12.6%) on protease inhibitor. The mean body mass index (BMI) was 23.7±4.7 with 9.2% underweight and 10% obese. The prevalence of osteopaenia and osteoporosis were 46.6% and 31.9% respectively, while 19.6% had normal bone mineral density (BMD). Osteoporosis was significantly higher in those aged above 40 years (p= 0.00001), the females (p= 0.022), the single (p=0.028) and the underweight (p=0.0001). There was no significant difference in BMD of those with or without protease inhibitor containing medications as well as treatment naïve patients.CONCLUSION:A high prevalence of abnormal bone mineral density was found in HIV positive patients in Nigeria. Patient age above 40 years and a body mass index class of underweight were significant associated factors. Routine bone mineral density assessment is recommended as an adjunct in the evaluation of HIV positive patients in Nigeria."